MEMAHAMI KONSEP MAṢLAHAH IMAM AL-GAZALI DALAM PELAJARAN USUL FIKIH - Darul Faizin (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Maṣlahah is an expression of taking advantage and rejecting harm, but that is not what is meant by al-Gazali; according to him, taking benefits and rejecting harm is human’s purpose, and humans good will be realized by achieving his goals. But what is meant by maṣlahah is maintaining the purpose of the Shari’a (al-muhāfaẓah ‘ala maqsūdi asy-syarī’ah). When dealing with texts (naṣ) maṣlahah is divided into three; there is a problem that is confirmed by the text (maṣlahah mu’tabarah), there is a problem that is canceled by the text (maṣlahah mulgah), and there is a problem that is unconfirmed and not canceled by the text (maṣlahah mursalah). Maṣlahah mursalah, when seen from the needs, are divided into three levels; first, the primary level (ḍarūriyāt) in the form of guarding religion (hifẓu ad-din), soul (hifẓu an-nafs), reason (hifẓu al-‘aql), descent (hifẓu an-nasl), and property (hifẓu al-māl) ), the second secondary level (hajiyāt) and the third tertiary level (tahsīniyāt). Maṣlahah mursalah can be used as a proposition for istimbāṭ by considering three characteristics, namely, maṣlahah is primary (ḍarūriyāt), certain (qath'iyyāt), and general (kulliyāt). According to al-Gazali, the purpose of the Shari’a (maqāsid asy-syarī’ah) can be known through the Qur’an, Sunnah, and consensus (ijma’). Then every maṣlahah that does not function to maintain the objectives of the Shari’a which is understood from the Qur’an, Sunnah, and the consensus (ijma') is a strange maṣlahah (gharībah), that is, a maṣlahah that is not in line with the Shari’a action, then the maṣlahah cannot be made into the proposition of legal discovery (istimbāṭ).